2013
DOI: 10.1093/jac/dkt411
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of cadazolid against clinically relevant Clostridium difficile isolates and in an in vitro gut model of C. difficile infection

Abstract: Cadazolid activity was greater than other tested antimicrobials against 100 C. difficile strains. Cadazolid effectively treated simulated CDI in a gut model, with limited impact on the enumerated gut microflora and no signs of recurrence or emergence of resistance within the experimental timeframe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
5
50
0
1
Order By: Relevance
“…This finding correlates well with the potent in vitro activity of CDZ against VRE and the low propensity of resistance development (12). The present results are also in line with a low impact of CDZ on the endogenous gut flora (14), possibly minimizing the creation of a niche used by VRE for colonization. The extent of the contribution of the gut flora sparing of CDZ to the low risk for VRE colonization in mice remains to be tested.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This finding correlates well with the potent in vitro activity of CDZ against VRE and the low propensity of resistance development (12). The present results are also in line with a low impact of CDZ on the endogenous gut flora (14), possibly minimizing the creation of a niche used by VRE for colonization. The extent of the contribution of the gut flora sparing of CDZ to the low risk for VRE colonization in mice remains to be tested.…”
supporting
confidence: 86%
“…Cadazolid (CDZ; ACT-179811), a new investigational antibiotic in development for the treatment of CDAD (10), exhibited efficacy and potency in prevention of CDAD similar or superior to VAN, MDZ, and FDX in the mouse model for CDAD (10,11). CDZ exhibited potent in vitro activity not only against C. difficile clinical isolates but also against VRE (MIC 90 , 2 g/ml) (12, 13), while having a limited impact on bacteria of the normal gut microflora in the in vitro human gut model (14). Recently, a phase 2 trial in CDAD showed clinical cure rates with CDZ treatment similar to those with VAN treatment, while having lower recurrence rates, resulting in higher sustained cure rates (15).…”
mentioning
confidence: 99%
“…Linezolid is not used to treat C. difficile infection, although the new oxazolidinone cadazolid is being evaluated as a promising therapeutic option to treat C. difficile infection (23,24). Cadazolid has shown very good activity against C. difficile strains (including some linezolid-resistant strains) in an in vitro gut model (23); however, in the studies cited, the molecular mechanisms of resistance to linezolid were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that a narrow-spectrum antibiotic with no or limited effect on members of the normal gut flora, notably the Bacteroides group, is an important factor for sustained treatment success against CDAD with less recurrence, as exemplified clinically for fidaxomicin (28). In an in vitro human gut model using therapeutic doses of cadazolid, the drug had very limited impact on the normal gut microflora, notably sparing the Bacteroides group (17). However, in the end clinical data will be needed to demonstrate the impact of cadazolid on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…1) currently in clinical development for CDAD. Cadazolid showed potent in vitro activity against C. difficile clinical isolates (15,16) and in a human gut model of CDAD, while having only a very limited impact on bacteria of the normal gut microflora (17). In phase 1 studies, this compound was well tolerated, with a very low systemic exposure resulting in a high concentration in the colon (18).…”
mentioning
confidence: 99%